Applying Modern Immunology to the Plague of Ancient Athens - Juhi C Patel (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
During the 5th century BCE, ancient Athens and Sparta were involved in a major war during which an epidemic disease broke out in Athens, claiming the lives of a substantial part of the population. Although the ancient Greek historian Thucydides provides a first-hand account of the symptoms of the plague, modern historians have not been able to definitively identify the pathogen that caused the deadly epidemic. In 1994, a burial tomb of Athens was unearthed that unveiled the likely remains of plague victims. In 2005, scientists conducted molecular testing on the dental remains and used suicide PCR to compare the ancient DNA to the DNA of seven probable modern diseases. They concluded that the bacterial DNA from the remains is related to a modern strain of Salmonella enterica serovar Typhi. However, these results do not entirely correlate to the primary literary evidence presented by Thucydides, or modern knowledge of the pathogenesis and epidemiology of typhoid fever. This study uses a formula derived from an SIR model (S for the number of susceptible people, I for the number of infections, and R for the number recovered or immune) to investigate how the refugee crisis at the beginning of the Peloponnesian War affected the spread of the plague. The results of the model help demonstrate how the rapid spread could have been slowed down or stopped through the adoption of protocols developed by modern immunologists.
Keywords: Athenian Plague; Plague of Athens; Thucydides; Peloponnesian War; disease modeling; SIR model